Mitigating policies for pollutant emissions in a DSGE for the Brazilian economy - Marcos Valli Jorge; Angelo M Fasolo; Silvio Michael de Azevedo Costa (Latin American Journal of Central Banking)
This paper examines the dynamic behavior of the Brazilian economy under policy regimes aimed at controlling pollutant emissions and limiting environmental damage. Greenhouse gas (GHG) emissions are assumed to be of two types: carbon from fossil resources burning for energy generation (i.e., thermoelectric) or carbon and non-carbon outputs from production processes (i.e., methane from cattle). Firms optimally decide on the demand for fossil and green energy, as the level of effort dedicated to abating emissions coming from production processes. Two alternative policies for emissions, which include emissions taxation (fixed cost) and emission permits trade (quantity caps), are introduced into an open-economy DSGE model for the Brazilian economy. Departing from the estimated parameters of the original version of the model, ratios in the new block of equations for the energy and emissions are calibrated using sectoral data, and some elasticities are set to reproduce the sensibility to some shocks implicit in the NGFS11 Network for Greening the Financial System. scenarios (Net Zero 2050). Simulations indicate neither of the emissions policies can induce transition in the energy matrix without a green investment policy. The approach adopted here is a first step in building a macroeconomic model capable of challenging scenarios from more specialized models dedicated to energy and emissions by better assessing possible effects and feedback related to the iterations with macroeconomic dynamics. Despite the difficulties concerning the limited availability of data in higher frequency, results indicate those modeling approaches are sufficiently flexible to incorporate the main aspects of energy and emission, serving as valuable tools for policy analysis.